Eilenberger, Wolfram (2021). El fuego de la libertad. El refugio de la filosofía en tiempos sombríos 1933-1943. Trad. J. Chamorro Mielke. Barcelona: Taurus, 384 pps. - Sánchez Matito, Manuel (Differenz. Revista internacional de estudios heideggerianos y sus derivas contemporáneas, 2022)
This is a review of the book The Fire of Freedom by Wolfram Eilenberger, a work in which the ideas and lives of four important philosophers of the 20th century are related: Simone Weil, Ayn Rand, Simone de Beauvoir and Hannah Arendt. The review focuses on the German author's study of the work and life of Hannah Arendt.